PENGARUH DISIPLIN DAN KOMPETENSI DOSEN TERHADAP PRESTASI MAHASISWA PROGRAM STUDI PENERBITAN - Benget Simamora (Jurnal Ilmiah Publipreneur, 2014)
The purpose of this study is to analyze how much the independent variables of discipline and competence of lecturer influence on student achievement Publishing department Creative Media State Polytechnic of Jakarta, either partially or simultaneously. Research subjects were 68 students. Each questionnaire consists of 15 questions for each study variable discipline, competence, and student achievement. To determine the influence of independent variables of discipline and competence on student achievement is determined by the regression equation, both multiple regression and simple regression. To determine the significance, the data obtained from the questionnaire was tested its validity through the validity, reliability, and test for normality. The data processing using SPSS software version 14. The results showed that (1) discipline positive and significant impact on student achievement with 99% accuracy, (2) the competence of lecturers positive and significant impact on student achievement with 99% accuracy, (3) discipline and competence of lecturer together positive and significant impact on achievement student with 95% accuracy.